‘It sounds like lived experience’: On empathy in rape trials - Bladini, Moa (International journal of law, crime and justice, 2023)
In this article the intrinsic relation between the formal and the informal aspects of rape trials in Sweden will be scrutinized and discussed, for two main reasons (that are intertwined). Firstly, rape cases are characterized by a word-against-word situation, with few other forms of evidence, and with a rate of convictions much lower than for other criminal cases. The fact that the parties’ statements are placed at the core of the presentation and assessment of the evidence leaves much scope for argumentation about normality, rationality, logic and common sense. Secondly, rape trials have been subject to a significant amount of critique, in public as well as in legal debate due to gendered stereotypes, assumptions about autonomy, objectivity, ideal victims, real rape etc. The article aims to explore and shed some light on parts of the continuum of formality and informality in criminal trials in Sweden. By deconstructing rape trials through the lens of the emotion-sociological concept of empathy, the article contributes to deepened knowledge of the work performed by the legal actors in court in general and their work as empathic translators, in particular. We will focus on a specific part of the empathic process, namely emotion management to stage credible testimonies, in the sense that the stories told by the parties and/or witnesses are framed and presented by legal professionals in court as if they have been acting and reacting normal, natural, reasonable and rational. We present the analysis of the intrinsic relationship between the formal framework and the informal work performed by the legal actors, by exploring how the legal concepts are embodied in stories from everyday life in the trial, framed by the legal actors. The analysis includes a description of the stage at which these trials take place (the objectivity ideals and self-images) and the most important formal aspects and parts of the criminal and procedural regulation of rape trials. The article ends with final conclusions and reflections on the continuum of formality and informality in rape trials. The material in the study from which this article derives consists of observations of 18 rape cases, including written judgments and interviews with legal professionals in these cases.